Analisis Hubungan Panjang Berat dan Pola Sebaran Littorina scabra (Gastropoda:Littorinidae) - Dayang Eka Pramayanti; Sendy L Merly; Sisca Elviana; Dandi Saleky (Musamus Fisheries and Marine Journal, 2022)
The purpose of this study was to analysis the length-weight relationship of gastropods (Family Littorinidae) which is associated with mangrove ecosystems where had a potential value to utilized for the management of natural resources in Merauke Regency. This research was conducted in June-August 2020 in the Mangrove Forest Ecosystem of Payum Beach, Merauke. The results show that an average weight of L. scabra 0.81 gr and average length of 1.85 cm, eventually for the length and weight analysis point towards Allometric Negative which means the growth of length is faster than the additional of body weight. The distribution pattern of L.scabra categorized uniform in all three station. This distribution patterns causing influenced by several factors such as food availability, substrates, ecological physical, chemical, enviromental factors, as well as adaptation strategies and biological interactions between population in the community.